Analysis of The Role of Cooperatives and MSME’s Sectors in The Empowerment of MSME’s in Medan City - Adriansyah Hidayat; Tri Inda Fadhila Rahma; Harahap, Muhammad Ikhsan (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
MSMEs are superior in absorbing labor by mobilizing local resources to support the regional economy. So that empowerment carried out by the government must be maximized so that MSMEs can be competitive. This study aims to analyze strategies at the Office of Cooperatives and MSMEs in Medan city in empowering and developing MSMEs using a qualitative approach using the N.Vivo application in the data processing process. The data collection techniques used are interviews and literature reviews related to the problem under study. The results of this study indicate that the strategy of the District Cooperative and MSME Office in empowering MSMEs has not run optimally. Because coaching from this government has not been felt by all MSME players in Medan City. Furthermore, MSMEs do not get capital assistance from the local government, and while there are still many MSMEs that have not received guidance from the government. In addition, the government has helped a little to overcome the problem of budget constraints by inviting participation from BUMN and the private sector in the implementation of MSME empowerment.